Augmented Reality in Physics Education: A Systematic Review of Its Potential, Challenges, and Future Research Directions - Erazando Alfa Seira; Apit Fathurohman; Hamdi Akhsan (Berkala Ilmiah Pendidikan Fisika, 2026)
The advancement of digital technology has driven the emergence of various educational innovations, one of which is Augmented Reality (AR), widely recognized for its potential to bridge the gap between abstract concepts and concrete experiences in physics education. Although numerous studies have demonstrated the benefits of AR, comprehensive reviews that critically examine its potential, challenges, and future research directions remain limited. This study employs a Systematic Literature Review (SLR) following the PRISMA framework, utilizing data sourced from ScienceDirect, IEEE Xplore, Google Scholar, and SINTA within the period 2020–2025. Of the 320 articles identified, 25 met the inclusion criteria and were subjected to thematic analysis. The findings reveal three major contributions of AR: enhancing conceptual understanding, strengthening critical thinking skills, and increasing learning motivation. The identified challenges include infrastructure limitations, teachers’ pedagogical readiness, and the absence of standardized evaluation frameworks. In practical terms, these findings have implications for physics teachers and curriculum developers. AR integration needs to be designed within an inquiry-based learning framework to support meaningful concept construction, not just visualization. In addition, AR module development must be structured, aligned with competency and assessment standards, and contextual. Further research should focus on the integration of AR with AI and the development of adaptive curricula in authentic learning. This review provides a comprehensive overview of AR’s role in supporting the transformation of 21st-century physics education, while also identifying opportunities for more focused and impactful future research.